Bcl-2/adenovirus E1B 19-kDa interacting protein (BNip3) has a key role in the mitochondrial dysfunction induced by mutant huntingtin. (10th September 2015) - Sassone, Francesca; Margulets, Victoria; Maraschi, AnnaMaria; Rodighiero, Simona; Passafaro, Maria; Silani, Vincenzo; Ciammola, Andrea; Kirshenbaum, Lorrie A.; Sassone, Jenny
Abstract : Huntington's disease (HD) is a neurodegenerative disorder caused by the expansion of a CAG repeat in the IT15 gene that encodes the protein huntingtin (htt). Evidence shows that mutant htt causes mitochondrial depolarization and fragmentation, but the underlying molecular mechanism has yet to be clarified. Bax/Bak and BNip3 are pro-apoptotic members of the Bcl-2 family protein whose activation triggers mitochondrial depolarization and fragmentation inducing cell death. Evidence suggests that Bax/Bak and BNip3 undergo activation upon mutant htt expression but whether these proteins are required for mitochondrial depolarization and fragmentation induced by mutant htt is unclear. Our results show that BNip3 knock-out cells are protected from mitochondrial damage and cell death induced by mutant htt whereas Bax/Bak knock-out cells are not. Moreover, deletion of BNip3 C-terminal transmembrane domain, required for mitochondrial targeting, suppresses mitochondrial depolarization and fragmentation in a cell culture model of HD. Hence, our results suggest that changes in mitochondrial morphology and transmembrane potential, induced by mutant htt protein, are dependent and linked to BNip3 and not to Bax/Bak activation. These results provide new compelling evidence that underlies the molecular mechanisms by which mutant htt causes mitochondrial dysfunction and cell death, suggesting BNip3 as a potential target for HD therapy.